The effect of protein-to-alginate ratio on in vitro gastric digestion of nanoparticulated whey protein. (February 2018) - Koutina, Glykeria; Ray, Colin A.; Lametsch, Rene; Ipsen, Richard
Abstract: The in vitro digestion of particles composed of nanoparticulated whey protein (unheated and heated for 85 °C for 10 min) and two types of alginate [low (40 kDa) and high (280 kDa) molecular mass] at ratios of 20:1 and 2:1 were evaluated under simulated gastric conditions at pH 3.0. The in vitro digestibility of nanoparticulated whey protein without addition of alginate was used as a control. The in vitro digestibility was characterised in terms of the amount of soluble peptide released in the supernatant after trichloroacetic acid precipitation, sodium dodecylsulphate-polyacrylamide electrophoresis and liquid chromatography-mass spectrometry. In addition, the zeta potential values of all mixtures at pH 3.0 were measured. Under simulated gastric conditions the nanoparticulated whey protein and alginate at a ratio of 2:1 showed the highest protection of whey proteins against pepsin digestion. Peptides derived from β-lactoglobulin 55–66 and 109–123 regions were resistant to 120 min of in vitro gastric digestion.